Effect of Anchovy Substrate of Stolephorus baganensis on Mutans Streptococci Isolated from Human Harbouring Species - Harun A Gunawan; Soeherwin Mangundjaja (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Anchovy fish is traditional food, which is beneficial for health, one of its benefits is capability to prevent dental caries because it has active substance of fluoride Objectives: The aim of the study was to determine the sensitivity of Anchovy substrate of Stolephorus baganensis on mutans of Streptococcus mutans. Methods: Anchovy substrate of Stolephorus baganensis was examined in vitro to inhibit the bacterial growth by determining the inhibition zone (agar diffusion method), minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC).The microorganisms tested were local strains of mutans of Streptococcus mutans isolated from human harbouring species in Untung Jawa Island Indonesia labeled as: Streptococcus mutans1, Streptococcus mutans2, Streptococcus mutans3, Streptococcus mutans4, Streptococcus .mutans5, Streptococcus mutans6.The statistical analysis was done by in a descriptive. Results: The MIC value 10%/ml,average of inhibition zone 1.90 mm for Streptococcus mutans1; The MIC value 10%/ml, average of inhibition zone 2.00 mm for Streptococcus mutans2; The MIC value 10%/ml ,average of inhibition zone 2.10 mm for Streptococcus mutans3 ; The MIC value 10%/ml , average of inhibition zone 3.50 mm for Streptococcus mutans4 ;The MIC value 10%/ml, average of inhibition zone 2.60 mm for Streptococcus mutans5;The MIC value 10%/ml, average of inhibition zone 1.50 mm for Streptococcus mutans6 and their MBC value was the same with MIC. Conclusion: This study shows that Anchovy substrate of Stolephorus baganensis, has antimicrobial activity against local strains of Streptococcus mutans isolated from human harbouring species